Launch of the European Wildlife Observatory platform at 13th international symposium on wild boar and other suids (IWBS 2022) ‐ 6‐9 September 2022. Issue 12 (16th December 2022) - ,; Guerrasio, Tancredi; Acevedo, P; Zanet, S; Vada, R; Blanco‐Aguiar, JA; Casaer, J; Jansen, P; Keuling, O; Plis, K; Podgórski, T; Preite, L; et al.
Abstract: The International Symposium on Wild Boar and Other Suids (IWBS 2022), which took place in Montseny Biosphere Reserve (Catalonia, Spain) in September 2022, provided to ENETWILD with the opportunity to meet in‐person for the first time after 2.5 years, and meet the international scientific community with expertise on wild suids and other ungulates. Twelve members of ENETWILD consortium representing 6 partners were present. Bringing together international experts, stakeholders and ENETWILD collaborators was a perfect occasion to present the European Observatory of Wildlife (EOW). Two hundred and twenty‐five wildlife experts from 25 countries were present at symposium, and at presentation of the EOW. Overall, 3 'Plenary Talks' and 118 presentations (62 oral and 56 posters) were made. The meeting has gone through all the possible topics regarding wild suids, from genetics to monitoring and management. This was the optimal context to introduce the EOW to an ideal target audience, both in terms of interest and in terms of potential new member of the Network. From our presentation, it emerged the importance of comparable data on geographical distribution and abundance of wildlife hosts in Europe, fundamental to develop the best management policies and to perform effective risk assessments for shared emergent diseases. The adoption of a common and effective protocol adopted throughout the continent would ensure such comparability. Moreover, the discussion highlighted the need of extending the network to as many European countries as possible and, when feasible, of having multiple sites within each country. A number of participants manifested their interest to join the EOW during the 2023 campaign. Such a capillary distribution of observation points would provide solid and comparable density estimates as well as effective feedback about the field protocol implemented by the EOW. A number of questions were raised by the audience during the presentation of the EOW.